Risco por inundação costeira na foz estuarina do rio Apodi-Mossoró/RN: aplicações de geotecnologias e simulações de mudanças climáticas - Aguiar, Leonlene de Sousa (2018)
The phenomenon of coastal flooding in estuarine areas is studied worldwide to understand the risks generated by low reliefs and plans where human communities exist, economic activities and constant transformation of morphologies and ecosystems. Climate change is not new and forecasting impacts from sea level rise is a matter of concern to countries, as trends indicate greater frequency of flooding with greater depths and proportionate losses. This research was carried out in the Apodi-Mossoró estuary, in the northern coast of the State of Rio Grande do Norte, Northeastern Brazil, with the objective of analyzing the risks generated by the coastal flood related to the high altitudes of the mesotide in an equatorial tropical hypersaline estuary with intense transformation by activities and human occupations. The research was based on geoprocessing techniques applied in remote sensing products with different spatial and temporal resolutions, observations of changes in land use and coverage, protected areas and wetlands, as well as the generation of information with precision and centimeter accuracy tracking with Global Navigation Satellite System and Remotely Piloted Aircraft to understand the hazards of flooding and areas under exposure, where it was necessary to work with digital photogrammetry procedures for digital surface model generation. The results point to saline activity as the main modifying agent of land use, resulting in the loss of permanent preservation areas, remaining 787.57 ha, and even so, approximately 1,907.09 ha of wetlands were lost in approximately 50 years . This picture contributes to the occurrence of coastal floods that affect 34.38 ha (16.29%) in the main city at the mouth of the estuary, in the city of Areia Branca / RN, interfering with the dynamics of more than 13 thousand people when the occurrence of floods by astronomical tide of syzygy of 3.8 meters combined with phenomena that rise 10 cm of the level of the sea. With the future trend of sea level rise, the flood area can reach 64.78 ha (30.69%) due to climate change. The flood reaches the special planning areas of Areia Branca defined by its Master Plan, and in addition to the other areas affected, it is estimated that economic damages are close to R$ 597,438.68 real or $ 147,152.37 ($ 1 = R$ 4.06 as of 09/1/2018).